Phosphorylation dynamics of membrane proteins from Arabidopsis roots submitted to salt stress. Issue 9 (20th March 2014) - Vialaret, Jérôme; Di Pietro, Magali; Hem, Sonia; Maurel, Christophe; Rossignol, Michel; Santoni, Véronique
<x xml:space="preserve">Abstract</x> An excess of NaCl in the soil is detrimental for plant growth. It interferes with mineral nutrition and water uptake and leads to accumulation of toxic ions in the plant. Understanding the response of roots to NaCl stress may facilitate the development of crops with increased tolerance to this and other stresses. Since controls achieved at the posttranslational level are of critical importance for regulating protein function, the present work used a robust label‐free quantitative proteomic methodology to quantify phosphorylation events that affect root membrane proteins in Arabidopsis, in response to short‐term (up to 2 h) NaCl treatments. This work identified 302 proteotypic phosphopeptides including 77 novel phosphorylated sites. NaCl treatment significantly altered the abundance of 74 phosphopeptides, giving novel insights into the regulation of major classes of membrane proteins, including ATPases, sodium transporters, and aquaporins. The data provide a unique access to phosphorylation reprogramming of ionic equilibrium in plant cells under NaCl stress. The use of predictive bioinformatic tools for kinase motifs suggested that root membrane proteins are substrates of cAMP‐dependent protein kinase, cGMP‐dependent protein kinase, and protein kinase C families, also called AGC kinases, arguing for an important role of lipid signaling in abiotic stress responses. It also pointed to cross‐talks between protein kinase families during NaCl stress.